Sistem Telemteri Data Pergeseran Tanah Dari Sensor Potensiometer Menggunakan Radio Frekuensi APC220 - Defi Setiawati; Gurum Ahmad Pauzi; W Warsito (Jurnal Teori dan Aplikasi Fisika, 2015)
This research has been realized a remote communication instrument using APC220 radio frequency as transmitter and receiver of landslide data that has controlled by Atmega32 microcontroller. Landslide sensor utilized bytwo potentiometersthat converting the shift distance into a voltage. The system used 10 WP solar cell and 12V 12Ah battery as a voltage source that can be operated in the isolated area for 15 hours. The computer receive voltage data and shift distance from system with interval 10 seconds. In this research, the sensor was able to detect 0 to 15 cm shift distance. First sensor has equation y = 0.275x + 0.138 with linear correlation 0.999 and sensitivity 0.235 V/cm meanwhile second sensor has equation y = 0.317 x - 0.677 with linear correlation 0.968 and sensitivity 0.270 V/cm.